ANALYSIS OF BUSINESS OPPORTUNITIES IN AN EFFORTS TO INCREASE COMMUNITY INCOME IN THE MARINA TOGO MOWONDU TOURISM AREA, WANGI-WANGI DISTRICT, WAKATOBI REGENCY - Munawir Makmur; Wa Ode Harliyanti Unga; Akbar Wahbi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze business opportunities in an effort to enhance community income in the Marina Togo Mowondu tourism area, Wangi-Wangi District, Wakatobi Regency. This research employs a qualitative descriptive approach, using data collection techniques such as in- depth interviews, observations, and document analysis. The participants involved in this study included local business operators, tourists, and relevant stakeholders. Data analysis was conducted using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the Marina Togo Mowondu tourism area possesses significant business potential in the culinary sector, souvenirs trade, transportation services, and tourism-based creative industries. The availability of natural tourism attractions, the increasing number of tourist visits, and active community participation serve as supporting factors for the development of these business opportunities. However, several constraints were identified, including infrastructure limitations, inadequate business management skills, and a lack of promotional strategies. Therefore, community capacity building, infrastructure improvement, and the optimization of digital marketing are required to foster business growth and ensure a sustainable increase in community income.